2007
DOI: 10.1039/b711478h
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent organometallic poly(aryleneethynylene)s: functional properties towards implications in molecular optoelectronics

Abstract: This article highlights recent progress in the development of rigid-rod metallopolyyne polymers of late transition metals which can exhibit easily tunable luminescent and electronic properties. Considerable focus is placed on the design strategies towards the tuning capability of phosphorescence emission color and optical bandgap of this class of luminescent metallopolymers, and the evaluation of their suitability as emitters in light-emitting applications, optical power limiters for sensor protection and semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
94
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 212 publications
(95 citation statements)
references
References 145 publications
(81 reference statements)
1
94
0
Order By: Relevance
“…deviations 0.06 and 68), [15,16,19,22,26,35] except for 4, for which the PtÀN lat and PtÀ C lat distances were calculated to be 2.170 and 1.998 , respectively (N lat and C lat are respectively the nitrogen atom of the lateral isoquinolinyl ring and the carbon atom of the lateral naphthyl ring directly coordinated to the Pt II ion). The corresponding X-ray data of 4 were reported to be 1.997 (8) and 2.088(5) , respectively. [22] However, the Pt À N lat distance is much longer (2.12(2) ) when the 4'-position of the central pyridyl ring of 4 is substituted with a phenyl ring.…”
Section: Opt Geometriesmentioning
confidence: 99%
See 1 more Smart Citation
“…deviations 0.06 and 68), [15,16,19,22,26,35] except for 4, for which the PtÀN lat and PtÀ C lat distances were calculated to be 2.170 and 1.998 , respectively (N lat and C lat are respectively the nitrogen atom of the lateral isoquinolinyl ring and the carbon atom of the lateral naphthyl ring directly coordinated to the Pt II ion). The corresponding X-ray data of 4 were reported to be 1.997 (8) and 2.088(5) , respectively. [22] However, the Pt À N lat distance is much longer (2.12(2) ) when the 4'-position of the central pyridyl ring of 4 is substituted with a phenyl ring.…”
Section: Opt Geometriesmentioning
confidence: 99%
“…As the energy separation between the spin-orbit-coupled S n and T m excited states has been correlated to the energy difference between the occupied d orbitals, [20,21] it has been reasoned that the closer the different occupied d orbitals are (the energy difference between two different occupied d orbitals is denoted Ddd occ ), the larger the H SOC matrix element and the faster the radiative decay rate constant k r will be, according to Equation (3). Indeed, the energetically closer proximity of the occupied d orbitals in the quasi-octahedral d 6 Ir III complexes (the t 2g orbitals) compared with the quasisquare planar d 8 Pt II complexes (d s and d p orbitals) has been put forward as the reason why the former are usually more intense emitters than the latter. [20,21] Thus, it is of interest to evaluate the d-orbital splittings between the two different highest lying occupied d orbitals (Ddd occ ) and the dd* splitting for 1-5.…”
mentioning
confidence: 97%
“…We have synthesize the 2-(2'-hydroxyphenyl)benzoxazole moiety (8) and appended this fluorescent moiety to the 8-Q ligand (9). Similarily, 1,4-divinylbenzene moiety was used to connect the substituted-benzoxazole adduct to the 8-quinolinolate ligand (10).…”
Section: Synthesis Of Substituted Benzoxazole Ligand For Electroopticmentioning
confidence: 99%
“…3 Ethynyl-bridge compounds have also been shown to have desirable luminescence qualities for an efficient photophysical PET process in metal compounds. [5][6][7][8] Very recently, Wong 61 reviewed the development of rigid-rod metallopolyyne polymers of the late transition metals and showed that the luminescent and electronic properties can be tuned by proper manipulation of the S 1 (singlet) and T 1 (triplet state) energy gap.…”
mentioning
confidence: 99%
“…The interest of alkynyl platinum(II) complexes stems from their rich structural diversity [1][2][3][4], their interesting chemical reactivity [1] and more recently from their increasing potential in material science [5][6][7][8][9][10][11][12][13][14][15][16][17]. In this field, light-emitting complexes have attracted a great deal of attention owing to their use in optoelectronic devices, chemosensors, photovoltaic cells and photocatalysis.…”
Section: Introductionmentioning
confidence: 99%